2011
DOI: 10.1159/000326109
|View full text |Cite
|
Sign up to set email alerts
|

Natural Evolution of Spitz Nevi

Abstract: Background: The natural evolution of melanocytic nevi is a complex, multifactorial process that can be studied by monitoring nevi on a long-term basis. Methods: To assess the evolution pathway of Spitz nevi, lesions with clinical and dermoscopic features suggestive of Spitz nevi were monitored and baseline and follow-up images compared. Results: Sixty-four patients (mean age 10.4 years) with lesions suggestive of Spitz nevi were included. Lesions were monitored for a mean follow-up period of 25 months. Upon si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 29 publications
1
39
0
1
Order By: Relevance
“…Pizzichetta et al also observed that after a variable number of months, lesions tended to acquire a stable homogeneous pattern. Finally, several months to a few years later, most lost their pigmentation and underwent spontaneous involution . A dermoscopic study by Argenziano et al on 64 Spitz nevi revealed that the majority of the lesions that were initially pigmented or partially pigmented during their growing phase (92.3%) became amelanotic or nonpigmented (47.1%) during their involution phase.…”
Section: Methodsmentioning
confidence: 99%
“…Pizzichetta et al also observed that after a variable number of months, lesions tended to acquire a stable homogeneous pattern. Finally, several months to a few years later, most lost their pigmentation and underwent spontaneous involution . A dermoscopic study by Argenziano et al on 64 Spitz nevi revealed that the majority of the lesions that were initially pigmented or partially pigmented during their growing phase (92.3%) became amelanotic or nonpigmented (47.1%) during their involution phase.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, our data show a significant association in these cases between IEM and intracorneal melanocytosis (p < 0.0001); furthermore, intracorneal melanocytes were relatively common in IEM-positive Spitz nevi (p = 0.0154). Regarding the high rate of spontaneous regression reported in Spitz nevi, 17,18 we surmise that intracorneal melanocytes may be an evidence of transepidermal elimination of melanocytes, which is considered as a potential route of regression. 19 Of course, macrophages can migrate into epidermis, ingest melanin there and turn into melanophages on site; however, our data suggest the intriguing possibility that some IEM may be dermal melanophages that have been transported into the epidermis together with dermal melanocytic nests during the process of transepidermal elimination of melanocytes.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, the potential for spontaneous involution of Spitz nevi has been emphasized. 17,18 The mechanism of involution in Spitz nevi is still uncertain, but transepidermal elimination of melanocytes is considered as one possibility. 19 The rate of transepidermal elimination of melanocytes is reportedly greater in Spitz nevi than in non-spitzoid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Involution as the natural evolution of Spitz nevi on the face, extremities, and trunk has been reported [5]. In the regression of pigmented skin lesions such as melanoma, fibrosis, melanosis, and numerous telangiectasis are histopathologically observed [6], but the combination of these features is not found in Spitz nevi.…”
Section: Resultsmentioning
confidence: 99%